PENDAMPINGAN PENGELOLAAN PAJAK BERBASIS APLIKASI BAGI UMKM DI KOTA PALEMBANG - Hidayat, Muhammad; Fuadah, Lukluk; Saggaf, Abdullah (LPPM IST AKPRIND Yogyakarta, 2021)
The main problem for MSMEs in fulfilling tax obligations is a lack of knowledgeand adequate human resources in completing administration in the taxation field. Thepurpose of this service is to provide assistance in tax management using tax applicationprovided by the DJP. The method of implementing this service is socialization in the form ofpresentations to MSMEs and assistance in the use of tax applications to MSME employeesin Palembang City. The result of this service is an increase in MSME understanding oftaxation and an increase in the ability of MSMEs to use applications in the field of taxation.